1999
DOI: 10.1128/aem.65.2.746-751.1999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Bacterial Strain Able To Degrade Branched Nonylphenol

Abstract: Conventional enrichment of microorganisms on branched nonylphenol (NP) as only carbon and energy source yielded mixed cultures able to grow on the organic compound. However, plating yielded no single colonies capable, alone or in combination with other isolates, of degrading the NP in liquid culture. Therefore, a special approach was used, referred to as “serial dilution-plate resuspension,” to reduce culture complexity. In this way, one isolate, TTNP3, tentatively identified as a Sphingomonas sp., was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(31 citation statements)
references
References 39 publications
4
26
1
Order By: Relevance
“…The results of the present study are consistent with previous reports of significant biodegradation of 4-NP under oxic conditions in seawater and sediment [19], in soil [20], and in cultures derived from sewage sludge [21][22][23][24][25]. Significant biodegradation of 4-NP was reported in sediments collected from a river in Taiwan and incubated under oxic conditions [26].…”
Section: Mineralization Under Oxic Conditionssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study are consistent with previous reports of significant biodegradation of 4-NP under oxic conditions in seawater and sediment [19], in soil [20], and in cultures derived from sewage sludge [21][22][23][24][25]. Significant biodegradation of 4-NP was reported in sediments collected from a river in Taiwan and incubated under oxic conditions [26].…”
Section: Mineralization Under Oxic Conditionssupporting
confidence: 92%
“…Little is known about the potential for, or the environmental conditions that may affect, the microbial degradation of 4-NP in stream sediments. Reports of significant biodegradation of 4-NP under oxic conditions in seawater and sediment [19], in soil [20], in cultures derived from sewage sludge [21][22][23][24][25], and in river sediments in Taiwan [26] suggest that biodegradation of 4-NP by stream-sediment microorganisms may be substantial. A number of studies concluding that 4-NP generally is recalcitrant in soil and sediments [9,13,16], however, suggest that efficient 4-NP biodegradation is not ubiquitous and is dependent on favorable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in which sphingomonad strains capable of xenobiotic degradation have been identified have used enrichment procedures from environmental samples collected from a single sampling location (e.g. Schmidt et al, 1992;Wittich et al, 1992;Tanghe et al, 1999). Clearly, sphingomonad communities acting in situ may be diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a ubiquitous organism that metabolizes organic compounds and estrogens, Novosphingobium aromaticivorans, found in soil, water, and coastal plain sediments, has been defined within the Sphingomonas family. [73][74][75][76][77][78][79] Importantly, two of the N. aromaticivorans proteins have the highest amino sequence homology with human PDC-E2 among all known bacteria. 80 Moreover, sera from PBC patients reacted against the two known lipoylated bacterial proteins from N. aromaticivorans lysate, with titers up to 10 À6 , including patients with early disease.…”
Section: Microbial Infection and Pbcmentioning
confidence: 99%